Using of essential oils in the treatment of mice infected with Trypanosoma evansi Uso de aceites esenciales en el tratamiento de ratones infectados con Trypanosoma evansi - Baldissera M.D. (2014)
Objective. This study aimed to test the effectiveness of copaiba, andiroba and aroeira essential oils for controlling trypanosomosis by Trypanosoma evansi with mice as experimental model. Materials and methods. Sixty-six mice were divided into eleven groups (A to L) with six animals each. Group A was the unique composed by healthy and uninfected animals (negative control). Animals in groups B to L were inoculated with 0.1 mL of blood containing 2.7 x 106 trypanosomes. Group B was used as a positive control without treatment. In experiment were tested copaiba (C, D and E), andiroba (F, G and H) and aroeira (I, J and L) oils at doses of 0.6, 0.8 and 1.0 mL kg-1 to infected mice (T. evansi). Results. These protocols did not provide curative efficacy; however, the mice treated with highest dose of copaiba showed a significant increase in the longevity when compared others groups. Conclusions. Previously in our studies, these essential oils have shown trypanocidal activity in vitro, but when they were tested in vivo in mice infected with T. evansi, this trypanocidal activity, or the curative effect was not found, being only able to prolong the lifespan of the animals treated with copaiba oil.